2021
DOI: 10.1007/s43452-021-00347-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the novel dieless clinching process free of blank holder

Abstract: A novel dieless clinching process free of blank holder was proposed in this study. This novel clinching process applied to joining Al5052 sheets under the forming forces from 24 to 54 kN was investigated experimentally. The joint geometrical characteristics, static mechanical strength, energy absorption and failure modes were revealed. From the results, the sound joints can be produced under various forming forces from 24 to 54 kN. With the forming force increasing, the neck thickness was increased continually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Figure 11 shows the geometric morphology of the joint obtained at different blank holder limit heights at the blank holder spring stiffness 500 N/mm. When the limited height of the blank holder is 1.4 mm, it is observed that the interlock length is small, the bottom protrusion is high, and there is a clear gap between the two sheets [30]. This is due to material mainly flow in the axial direction without restriction.…”
Section: With the Blank Holder Limitedmentioning
confidence: 98%
See 2 more Smart Citations
“…Figure 11 shows the geometric morphology of the joint obtained at different blank holder limit heights at the blank holder spring stiffness 500 N/mm. When the limited height of the blank holder is 1.4 mm, it is observed that the interlock length is small, the bottom protrusion is high, and there is a clear gap between the two sheets [30]. This is due to material mainly flow in the axial direction without restriction.…”
Section: With the Blank Holder Limitedmentioning
confidence: 98%
“…Besides, Response Surface Methodology is used to predict the optimal joint, with the limitation of the blank holder, a dieless clinched joint with interlock of 0.16 mm and protrusion height of 1.0 mm can be achieved. From [30], Chen et al investigated the novel dieless clinching process free of blank holder by experimental methods, mechanical interlock value can be reached to 0.18 mm. Comparing these two results, it is seen that our result is consistent with the research result from Chen.…”
Section: Effect Of the Blank Holder Limitedmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the above limitation, some scholars attempted to reduce or eliminate the exterior protrusion by improving the mould structure or optimising the joining process. The optimised processes such as dieless clinching [30], flat-clinching [31], reshaping process [32] and dieless clinching process free of blank holder [33] were wildly employed to enhance the joint static strength, improve the mechanical performance and reduce the exterior protrusion height of conventional clinched joint. Moreover, for the irreplaceable feature of the failed clinched joints, that is, when the clinched joints served a long time or subjected to fatigue loads in a period time, the clinched joint cracks or breaks, and the most common solution is to replace it with a new clinched joint.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, various thin sheet joining techniques were reported, such as clinching, 7 self-piercing riveting (SPR), 8 bonding, 9 stir friction welding, 10 and resistance spot welding (RSW). 11 Clinching technology plastic deformation under pressure to form mosaic points.…”
Section: Introductionmentioning
confidence: 99%